If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying C + ax = b + -1dx Solving C + ax = b + -1dx Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-1ax' to each side of the equation. C + ax + -1ax = b + -1ax + -1dx Combine like terms: ax + -1ax = 0 C + 0 = b + -1ax + -1dx C = b + -1ax + -1dx Reorder the terms: C = -1ax + b + -1dx Simplifying C = -1ax + b + -1dx
| 6x+3=-37+2x | | 9x+8=68+3x | | B=-1+3a | | 2(x-5)-3(2t-7)=12-5(3t+1) | | 30-8x=15-5x | | 2u+4=u-7 | | 5+4(3c-1)= | | 2(5x+2)=3x-17 | | 4(3x-4)+8=4x+32 | | 22=2(2x-1) | | 2x+23=5x+35 | | 7x+20=76 | | -3x-5=2(x-5) | | .30+1.19=2.99 | | 3.00+8.0=6.75 | | 15x-2*(5x-3)=2*(x+9) | | 4(36-12h+h^2)-18+3h-(144-18)= | | -7+3x=-34 | | 28-3c=14 | | 5=6x-1 | | y=x^4+1x^2-30 | | P=20-5Q | | x^4+1x^2-30=0 | | (10x+9)=3 | | 3*5*6=153072 | | 5x-7=7x+6 | | 58=10x+8 | | 64x^4-27x=0 | | 11.5-8.5= | | 0=x^2-21x+24 | | 8-0.5(x+3)=0.25(x+-1) | | -(4-m)=10 |